Development of health massage to improve working productivity with Daksa disabilities - Sumarjo Sumarjo; Sigit Nugroho; Aris Fajar Pambudi (MEDIKORA, 2020)
This development research by modifying the form of massage. The phase being developed is related to health massage which is expected to increase productivity and provide suitable techniques for disabled persons with lower limbs. The research objective is to develop a form of health massage so that it can increase work productivity for persons with disabilities. The specific target in the research is to find the right health massage techniques and patterns for people with disabilities in increasing work productivity. The target of this research is designed through three stages, namely survey research, development research, and experimental research. The subjects of the study were persons with disabilities with monoplegia disabilities in Yogyakarta Special Region. Based on the research results, it can be concluded that the perception of the form of health massage is very good and feasible to be applied. In addition, massage is effective for dealing with health and overcoming complaints of pain. The specifications for the form of health massage are body position consisting of three positions, namely face down on your back and sitting. In a prone position starting from the left starting from the bottom, namely the left leg. In the supine position massage starts from the left foot and toes. In a sitting position massage starts from the right shoulder. The techniques used from these three positions use friction, petrisage, tapotement, walken, skin rolling and effleurage. In addition, the massage applied is safe for persons with disabilities, safe in dealing with health and safe for increasing work productivity which consists of motivation, knowledge, skills, and attitudes. Pengembangan masase kesehatan untuk meningkatkan produktivitas kerja disabilitas Tuna Daksa Penelitian pengembangan ini dengan memodifikasi bentuk masase. Masase yang dikembangan berkaitan dengan masase kesehatan yang diharapkan dapat meningkatkan produktivitas dan memberikan teknik yang sesuai untuk disabilitas tuna daksa yang mengalami cacat bagian bawah. Tujuan penelitian untuk mengembangkan bentuk masase kesehatan sehingga dapat meningkatkan produktivitas kerja bagi penyandang disabiliatas tuna daksa. Target khusus dalam penelitian menemukan teknik dan pola masase kesehatan yang tepat bagi para disabiliatas tuna daksa dalam meningkatkan produktivitas kerja. Target penelitian ini dirancang melalui tiga tahap yaitu penelitian survey, penelitian pengembangan, dan penelitian eksperimental. Subyek penelitian penyandang disabilitas tuna daksa monoplegia di Daerah Istimewa Yogyakarta. Berdasarkan hasil penelitian dapat disimpulkan bahwa persepsi bentuk masase kesehatan sangat baik dan layak untuk diterapkan. Selain itu masase yang diterapkan efektif untuk mengatasi kesehatan serta mengatasi keluhan rasa sakit. Spesifikasi bentuk masase kesehatan yaitu posisi badan terdiri dari tiga posisi, yaitu telungkup terlentang dan duduk. Pada posisi telungkup dimulai dari sebelah kiri diawali dari bawah yaitu bagian kaki kiri. Pada posisi terlentang masase diawali dari kaki dan jari-jari kaki sebelah kiri. Pada posisi duduk masase diawali dari bahu sebelah kanan. Teknik yang dipakai dari ketiga posisi tersebut menggunakan friction, petrisase, tapotement, walken, skin rolling dan effleurage. Selain itu masase yang diterapkan aman untuk penyandang disabilitas tuna daksa, aman dalam mengatasi kesehatan dan aman untuk meningkatkan produktifitas kerja yang teridiri dari motivasi, pengetahuan, keterampilan, dan sikap.